Taxi functions of German deverbatives: potential and realized - I. V. Arkhipova (Гуманитарные и юридические исследования)
Introduction. Modern researchers describe deverbatives as «dual» names, derivatives of various lexical and derivational semantics, preserving the semantic properties of generating verbs.   The purpose of this work is to study such verbal characteristics as taxis, i.e. the ability to actualize various taxis meanings of simultaneity and diversity of explicated actions in predicative constructions.   Materials and Methods. The material of the study was German utterances with deverbatives obtained by directed sampling from the database of the Leipzig Corpus (LC) and the Electronic Dictionary of the German Language (DWDS). In the course of the study, a hypothetical-deductive, inductive and descriptive method was used, including methods of observation, comparison, generalization, classification and interpretation of linguistic phenomena.   Analysis. This article deals with German deverbatives characterized by various taxis functions (potential and realized). The potential functions of deverbatives are realized in a certain taxis environment (primary taxis or secondary taxis). Various prepositions of temporal and other adverbial (modal, instrumental, medial, causal, conditional, final) semantics act as prototypical constituents of the taxis environment.   Results. Based on the results of the study, we can conclude that when used with temporal prepositions, deverbatives implement the primary-taxis functions of simultaneity or non-simultaneity, and when combined with modal, instrumental, medial, conditional, causal, and other prepositions, they implement the secondary-taxis functions of simultaneity. The constitutive composition of the taxis environment determines the «speech behavior» of deverbatives. Some German deverbatives are distinguished by dual «speech behavior», which manifests itself in the conditions of a primary-taxis or secondary-taxis environment. Genetically-multiplicative and genetically-iterative names implement multiplicative-taxis, iterative-taxis or semelfactive-taxis values. In addition, in a certain contextual environment, their iterative-taxis function may remain unrealized.